THE IMPORTANCE OF SPIRITUAL AND EDUCATIONAL EVENTS HELD IN STUDENT RESIDENCES IN INCREASING THE SOCIAL ACTIVITIES OF YOUTH (International Educators Conference, 2025)
This article provides a detailed analysis of various events organized in student dormitories and their importance in the formation of a harmonious generation, the goals and objectives of these events, as well as their results, using the example of Karshi State University.